Evolutionary psychology 101 - Geher, Glenn (Psych 101 series., 2014)
"This is a concise and student-friendly survey of the burgeoning field of evolutionary psychology (EP) and the controversies that surround it. Evolutionary psychology is an approach to studying human behavior that is rooted in modern evolutionary theory. Firmly grounded in the theoretical and research literature of EP, the book addresses the core theories, approaches, applications, and current findings that comprise this discipline. It is unique in its interdisciplinary focus, which encompasses EP's impact on both psychological and non-psychological disciplines. Written by an eminent evolutionary psychologist who is President of the Northeastern Evolutionary Psychology Society, the text examines psychological processes that lead to human survival and those that may lead to reproductive benefits-sometimes even at a cost to survival. It cites a rich body of literature that provides insights into the role of sexual selection in shaping the human mind. The text presents current research on such important domains of EP as childhood, courtship, intrasexual competition, sex, pair-bonding, parenting, familial relations, non-familial relations, aggression, and altruism. Considering the potential of EP to mitigate some of our greatest social problems, the text examines the ways in which EP can be applied to society and religion. It also offers a thoughtful, balanced approach to such controversies in EP as the issues of genetic determinism, racism, and sexism."--Publisher's website